Outcomes of symptomatic venous thromboembolism after haploidentical donor hematopoietic stem cell transplantation and comparison with human leukocyte antigen-identical sibling transplantation. Issue 194 (October 2020) - Zhang, Gao-Chao; Zhang, Yuan-Yuan; Zeng, Qiao-Zhu; Meng, Xing-Ye; Zhao, Peng; Fu, Hai-Xia; He, Yun; Zhu, Xiao-Lu; Mo, Xiao-Dong; Wang, Jing-Zhi; Yan, Chen-hua; Wang, Feng-Rong; et al.
Abstract: Background: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is regarded as a curative therapy for majority of hematologic malignancies and some non-malignant hematologic diseases. Venous thromboembolism (VTE) has become increasingly recognized as a severe complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Objectives: To show the characteristics of VTE after haploidentical donor hematopoietic stem cell transplantation (HID-HSCT) and make comparisons with matched related donor HSCT (MRD-HSCT). Patients/methods: A retrospective nested case-control study design was used, cases with VTE and matched controls were selected, with 3534 patients underwent HID-HSCT and 1289 underwent MRD-HSCT. Results: During follow-up, 114 patients with VTE were identified. The incidence of VTE in HID-HSCT group was similar to that of MRD-HSCT group (2.4% versus 2.3%, P  = 0.92). In HID-HSCT group, VTE occurred at a median time of 92.5 days, which was earlier than MRD-HSCT group (243.5 days). For HID-HSCT, advanced disease status, cardiovascular risk factors, acute graft-versus-host disease (aGVHD), and relapse were the independent risk factors for VTE. For MRD-HSCT, cardiovascular risk factors, aGVHD, and relapse were associated with VTE. Overall survival (OS) of patients following HID-HSCT and MRD-HSCT were similar, but the OS in patients with VTE was significantly lower than patients without VTE. Conclusions: There was no statistical difference in the incidence of VTE after HID-HSCT compared with MRD-HSCT. The development of VTE adversely impacted the OS after allo-HSCT. Highlights: The incidence of VTE in HID-HSCT is similar to that in MRD-HSCT. Prior VTE, cardiovascular risk factors, GVHD and relapse are associated with VTE after allo-HSCT. The development of VTE adversely impacts overall survival after allo-HSCT.